2003
DOI: 10.1007/s00198-002-1316-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent vertebral deformities predict increased mortality and increased fracture rate in both men and women: A 10-year population-based study of 598 individuals from the Swedish cohort in the European Vertebral Osteoporosis Study

Abstract: The aim of this study was to evaluate whether a prevalent vertebral deformity predicts mortality and fractures in both men and women. In the city of Malmö, 598 individuals (298 men, 300 women; age 50-80 years) were selected from the city's population and were included in the Swedish part of the European Vertebral Osteoporosis Study (EVOS). At baseline the participants answered a questionnaire and lateral spine radiographs were performed. The prevalence of subjects with vertebral deformity was assessed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
2
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(153 citation statements)
references
References 42 publications
2
135
2
12
Order By: Relevance
“…However, studies focusing on symptomatic fractures have a disadvantage in that only one-third of all vertebral fractures come to clinical attention (46). Identifying prevalent vertebral fractures is important, since prevalent vertebral deformities are associated with reduced quality of life (47), an increased mortality rate, and an increased risk of future fractures in the general population (48).…”
Section: Epidemiology and Etiology Of (Prevalent) Vertebral Fracturesmentioning
confidence: 99%
“…However, studies focusing on symptomatic fractures have a disadvantage in that only one-third of all vertebral fractures come to clinical attention (46). Identifying prevalent vertebral fractures is important, since prevalent vertebral deformities are associated with reduced quality of life (47), an increased mortality rate, and an increased risk of future fractures in the general population (48).…”
Section: Epidemiology and Etiology Of (Prevalent) Vertebral Fracturesmentioning
confidence: 99%
“…M any studies have shown increased fracture risk (1)(2)(3) and mortality (4)(5)(6)(7)(8) after clinical vertebral fracture. Even subjects with no clinical fracture and little pain but with vertebral deformity detected by X-ray showed slightly increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…These fractures are estimated to affect at least 20% of the elderly population [1][2][3]; however, only 30-40% of these come to clinical attention [4,5]. Vertebral fractures have been associated with increased mortality in several studies [6][7][8][9][10][11][12][13], but obvious associations with specific causes of death have so far not been reported. Increased mortality has also been found to be independently associated with low bone mineral density without fractures [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Deaths from cardiovascular diseases in men and malignant neoplasms and respiratory diseases in men and women have been suggested to explain the excess mortality in subjects with vertebral fracture [9,11,13], whereas low bone mineral density has been linked with increased risk of stroke and also with mortality from natural causes other than cardiovascular diseases [14][15][16]. Vertebral fractures are known to predict the risk of subsequent hip fracture [17][18][19], but associations with deaths due to injuries have not been reported.…”
Section: Introductionmentioning
confidence: 99%